E-Learning Adoption in Higher Education Institutions During the COVID-19 Pandemic: A Multigroup Analysis - Shams, Muhammad Shahid; Niazi, Murtaza Masud; Gul, Habib; Mei, Tang Swee; Khan, Kaleem Ullah (Frontiers in Education, 2022)
Using the DeLone and McLean (D&M) Model, the study explains the differences between female and male students’ accessibility to E-learning portals. This study compares female and male student groups regarding the usage of the E-learning portal in the higher education context. Using an online google survey, the data were collected from 254 students, including males and females. The study utilized PLS-SEM to perform a multi-group analysis examining female and male student groups. The multi-group analysis followed the MICOM procedure, and SmartPLS three was utilized to analyze the data. The study found a significant and direct relationship of E-service quality with system use and user satisfaction. System quality also supported the relationship with user satisfaction. The study further revealed a significant and positive relationship between system use and user satisfaction with E-learning portal success. This study found a direct relationship between system quality and user satisfaction with the E-learning portal success in the female model. This study also concluded that a difference exists in using the E-learning portal between female and male student in higher education institutions. Keywords – COVID-19, E-learning portal success, Gender, Higher education institutions, Afghanistan, PLS-MGA